Effect of sintering temperature on physical, structural and optical properties of wollastonite based glass-ceramic derived from waste soda lime silica glasses - Amer Almasri, Karima; Ab Aziz, Sidek; Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz (Elsevier, 2017)
The impact of different sintering temperatures on physical, optical and structural properties of wollastonite (CaSiO3) based glass-ceramics were investigated for its potential application as a building material. Wollastonite based glass-ceramics was provided by a conventional melt-quenching method and followed by a controlled sintering process. In this work, soda lime silica glass waste was utilized as a source of silicon. The chemical composition and physical properties of glass were characterized by using Energy Dispersive X-ray Fluorescence (EDXRF) and Archimedes principle. The Archimedes measurement results show that the density increased with the increasing of sintering temperature. The generation of CaSiO3, morphology, size and crystal phase with increasing the heat-treatment temperature were examined by field emission scanning electron microscopy (FESEM), Fourier transforms infrared reflection spectroscopy (FTIR), and X-ray diffraction (XRD). The average calculated crystal size gained from XRD was found to be in the range 60 nm. The FESEM results show a uniform distribution of particles and the morphology of the wollastonite crystal is in relict shapes. The appearance of CaO, SiO2, and Ca-O-Si bands disclosed from FTIR which showed the formation of CaSiO3 crystal phase. In addition to the calculation of the energy band gap which found to be increased with increasing sintering temperature.